A Novel Hybrid Cascaded and Stacked Coupled Inductor Boost Converter With Active Clamping Zero-Voltage Switching - Jing-Yuan Lin; Chuan-Ting Chen; Yi-Feng Lin (IEEE Access)
The application of a traditional boost converter requires a wide duty cycle for high boost voltage gain. The wide duty cycle has the problem of a high current peak due to a large input current. The Coupled inductor based boost converter achieves a high step-up voltage ratio and reduce the problem of wide duty cycle. However, the basic coupled inductor converters have some disadvantages. Such as high voltage spike on the switch caused by a leakage inductance and the problem of large input current still cannot effectively improve. This paper aims to address these problems. The proposed topology used a coupled inductor to achieve high step-up voltage ratio. The designed voltage stabilizing capacitor loop reduces the current peak value of the main coupling inductor. Active clamping is used to suppress voltage spikes and implement zero-voltage switching (ZVS) of the switch to improve efficiency. This study describes the working principle and time domain analysis of this topology. Detailed design of components and propose the best design process. A prototype converter with an output power of 400 W was constructed. Conducted at a DC input voltage of 40 VDC and a DC output voltage of 400 VDC. Experimental results show that the maximum conversion efficiency is 94.6%.